Pengembangan Bahan Ajar Berbasis Audio Visual Pada Mata Pelajaran Boga Dasar - Dewi Gita Astuti; Sri Wahyu Andayani (Universitas Sarjanawiyata Tamansiswa, 2023)
ABSTRACT The objectives of this study are: (1) Produce audio-visual learning media for making basic spices in Indonesian cuisine (2) Knowing the feasibility of video learning media for making basic spices in Indonesian cuisine (3) Knowing student responses to the use of audio-visual media for making basic spices in Indonesian cuisine class X at SMK N 1 Kalasan for the academic year 2021/2022. This type of research is research and development that refers to the Brog and Gall development model using 10 stages of development. Data analysis technique with descriptive analysis. Data was collected by observation, interviews and questionnaires. Product validation involves material experts, media experts and students. Test the validity using a Likert scale. The results showed: (1) The procedure in the preparation of this media there are 10 stages, namely: potential problems, product design, design validation, design revisions, product trials, product revisions, usage trials, product revisions, mass production. (2) The results of video media validation by material experts show a percentage of 93.75% (very feasible), media experts with a percentage of 93.18% (very feasible). (3) The results of the feasibility with a small-scale trial with 6 students 90.41% (very feasible) and a limited scale test with 26 students 83.84% (very feasible). Keywords: Media, Videos, Basic Ingridients.